2021
DOI: 10.1155/2021/6686517
|View full text |Cite
|
Sign up to set email alerts
|

UGT1A1 Polymorphism for Irinotecan Dose Escalation in Patients with BRAF-Mutated Metastatic Colorectal Cancer Treated with First-Line Bevacizumab and FOLFIRI

Abstract: Background. Patients with metastatic colorectal cancer (mCRC) and BRAF V600E mutation have a poor prognosis, with a median progression-free survival (PFS) of only 5–7 months after initial therapy. The current standard first-line chemotherapy for these patients includes FOLFOX or FOLFIRI plus bevacizumab. In this study, we explored the effects and oncological outcomes of UGT1A1 polymorphism for irinotecan escalation in patients with BRAF-mutated mCRC. Patients and Methods. This retrospective study included 17 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Another compelling question is whether primary tumor location affects the outcome in BRAF-mutated mCRC treated with triplet therapy. Although the role of tumor location in the prognosis of BRAF-mutated mCRC remains controversial [16,21], it may have some impact with the concomitant use of target therapy such as bevacizumab or cetuximab [22]. Several studies have demonstrated that first-line bevacizumab plus chemotherapy resulted in a superior prognosis for right-sided BRAF-mutated mCRC [16,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another compelling question is whether primary tumor location affects the outcome in BRAF-mutated mCRC treated with triplet therapy. Although the role of tumor location in the prognosis of BRAF-mutated mCRC remains controversial [16,21], it may have some impact with the concomitant use of target therapy such as bevacizumab or cetuximab [22]. Several studies have demonstrated that first-line bevacizumab plus chemotherapy resulted in a superior prognosis for right-sided BRAF-mutated mCRC [16,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of tumor location in the prognosis of BRAF-mutated mCRC remains controversial [16,21], it may have some impact with the concomitant use of target therapy such as bevacizumab or cetuximab [22]. Several studies have demonstrated that first-line bevacizumab plus chemotherapy resulted in a superior prognosis for right-sided BRAF-mutated mCRC [16,[23][24][25]. Conversely, leftsided mCRC had more favorable outcomes when treated with anti-EGFR agents than did right-sided tumors [22,26], which was consistent with our observation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, our prospective, randomized study also suggested that if patients with mCRC, regardless of their KRAS gene status, receive UGT1A1 genotyping, they can tolerate escalated doses of irinotecan and potentially achieve a more favorable clinical outcome without signi cantly increased toxicity [9,12]. Furthermore, the oncological outcomes of patients with BRAF-mutated mCRC treated using FOLFIRI plus bevacizumab with irinotecan dose escalation as a rst-line therapy are acceptable with tolerable adverse events; this approach may be a feasible treatment option for such patients [10]. In the current retrospective study, we investigated the clinical outcomes of patients with PC-only mCRC who received rst-line bevacizumab and FOLFIRI with irinotecan dose escalation according to UGT1A1 polymorphism.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, this study was a retrospective review of 206 patients with mCRC, and written informed consent was obtained from all patients (KMUHIRB-E(I)-20200036). The responses were classi ed by a radiologist according to RECIST Version 1.1 [10]. DNA extraction for direct sequencing of KRAS/NRAS and immunohistochemical (IHC) analysis of epidermal growth factor receptor (EGFR) expression were performed using the methods described in our previous study [9].…”
Section: Introductionmentioning
confidence: 99%